2015
DOI: 10.1159/000430993
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Measurement of Serum Vascular Endothelial Growth Factor in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: Impaired vascular endothelial growth factor (VEGF) signaling causes emphysema in animal models. In chronic obstructive pulmonary disease (COPD) patients, alterations in VEGF tissue expression have been observed. We hypothesize that circulating VEGF may be a biomarker to phenotype COPD patients. Objective: The aim of this study was to investigate VEGF serum levels in stable and exacerbated COPD. Methods: VEGF serum levels as well as parameters of short- and long-term outcome were assessed and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
9
2
2
Order By: Relevance
“…This is in line with what is known for hepatitis and diabetes, where the SNP rs8099917 GG genotype is considered to be the risk genotype and the SNP rs12979860 CC genotype the protective genotype [35][36][37]. The IFNL3 polymorphisms predict response to treatment in patients with hepatitis C [27,30,31]. We found that the prevalence of malignancy was increased among patients with the rs8099917 GG genotype.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in line with what is known for hepatitis and diabetes, where the SNP rs8099917 GG genotype is considered to be the risk genotype and the SNP rs12979860 CC genotype the protective genotype [35][36][37]. The IFNL3 polymorphisms predict response to treatment in patients with hepatitis C [27,30,31]. We found that the prevalence of malignancy was increased among patients with the rs8099917 GG genotype.…”
Section: Discussionsupporting
confidence: 86%
“…1). Details of inclusion and exclusion criteria were previously published [27]. We analysed data from 528 patients, who completed the first 6 month-follow-up of the study and for whom serum samples from visit 1 were available.…”
Section: Study Overviewmentioning
confidence: 99%
“…COPD patients with chronic bronchitis had increased VEGF levels in sputum in contrast to COPD patients with emphysema who had decreased VEGF levels . Patients with acute exacerbations presented high levels of VEGF in the circulation compared with stable COPD patients and healthy subjects, and increasing circulating VEGF longitudinal course appears to be related to poorer COPD prognosis . In this study, all the VEGFR were expressed by the lung fibroblasts, and especially VEGFR3, which has not previously been shown.…”
Section: Discussioncontrasting
confidence: 49%
“…Vascular endothelial growth factor (Boeck et al., 2015), free radicals (Rossman et al., 2013), matrix metalloproteinase‐9 (Vlahos et al., 2012), and systemic inflammation (Furutate et al., 2016) have been found to play a role in the modulation of BBB permeability after hypoxic stress in COPD. The vascular endothelial growth factor‐mediated increase in BBB permeability involves nitric oxide‐ and cGMP‐dependent pathways (Schoch et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia can induce the release of vascular endothelial growth factor (Boeck et al., 2015), free radicals (Rossman et al., 2013), and proteolytic enzymes matrix metalloproteinase‐9 (Vlahos, Wark, Anderson, & Bozinovski, 2012). Systemic inflammation is also present in patients with COPD (Furutate et al., 2016).…”
Section: Introductionmentioning
confidence: 99%